All work, no pay : finding an internship, building your resume, making connections, and gaining job experience - Berger, Lauren (Lauren E.) (Tantor Media, 2019)
Land killer internships-and make the most of them!These days, a college resume without internship experience is considered "naked." Indeed, statistics show that internship experience leads to more job offers with higher salaries-and in this tough economy, college grads need all the help they can get. Enter Lauren Berger, internships expert and CEO of Intern Queen, Inc., whose comprehensive guide reveals insider secrets to scoring the perfect internship, building invaluable connections, boosting transferable skills, and ultimately moving toward your dream career. She'll show you how to: - Discover the best internship opportunities, from big companies to virtual internships- Write effective resumes and cover letters- Nail phone, Skype, and in-person interviews- Know your rights as an intern- Use social networking to your advantage- Network like a pro- Impress your boss- Get solid letters of recommendation- Turn internships into job opportunities With exercises, examples, and a go-getter attitude, this next-generation internship manual provides all the cutting-edge information students and recent grads will need to get a competitive edge in the job market. So what are you waiting for'